2015
DOI: 10.1080/15592324.2015.1031938
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum ions alter the function of non-specific phospholipase C through the changes in plasma membrane physical properties

Abstract: The first indication of the aluminum (Al) toxicity in plants growing in acidic soils is the cessation of root growth, but the detailed mechanism of Al effect is unknown. Here we examined the impact of Al stress on the activity of non-specific phospholipase C (NPC) in the connection with the processes related to the plasma membrane using fluorescently labeled phosphatidylcholine. We observed a rapid and significant decrease of labeled diacylglycerol (DAG), product of NPC activity, in Arabidopsis seedlings treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Aluminum also reduced PC-derived DAG production in Arabidopsis and this was rescued by NPC4 overexpression and npc4 was more sensitive to aluminum stress [150]. The aluminum-decreased NPC activity in Arabidopsis was later found to be through aluminum-induced changes in plasma membrane physical properties [151]. NPC activity was down-regulated in parsley cells by a glycoprotein elicitor from Phytophthra sojae and in tobacco cells by the small protein cryptogein from Phytophthra cryptogea [147].…”
Section: Substrate Preference and Regulation Of Npc Activitiesmentioning
confidence: 99%
“…Aluminum also reduced PC-derived DAG production in Arabidopsis and this was rescued by NPC4 overexpression and npc4 was more sensitive to aluminum stress [150]. The aluminum-decreased NPC activity in Arabidopsis was later found to be through aluminum-induced changes in plasma membrane physical properties [151]. NPC activity was down-regulated in parsley cells by a glycoprotein elicitor from Phytophthra sojae and in tobacco cells by the small protein cryptogein from Phytophthra cryptogea [147].…”
Section: Substrate Preference and Regulation Of Npc Activitiesmentioning
confidence: 99%
“…To date, physiological roles for four of these NPC isoforms have been described, excepting NPC2 and NPC6. NPC4 and NPC5 play a role in response to phosphate starvation (Nakamura et al ., ; Gaude et al ., ) and salt stress (Peters et al ., , ; Kocourkova et al ., ), NPC4 in aluminum toxicity (Pejchar et al ., , ; Pejchar & Martinec, ), NPC3 and NPC4 in brassinolide signaling (Wimalasekera et al ., ), and NPC1 in the heat stress response (Krčková et al ., ). Thus, while the involvement of NPCs in stress responses is well described, it is not known whether NPCs are involved in reproductive development.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum ion (Al) is a major toxic factor in acidic soils that affects crop production. Using tobacco BY-2 cells incubated with fluorescent PC, AlCl 3 treatment reduced content of fluorescent DAG, which was more enriched in plasma membrane fraction than in microsomal fraction (Pejchar and Martinec 2015 ; Pejchar et al 2010 ). GUS reporter assay showed that NPC4-GUS expression was reduced after AlCl 3 treatment in root, and knockout mutant of NPC4 showed higher sensitivity to AlCl 3 -induced stress than wild type (Pejchar et al 2015 ).…”
Section: Emerging Functions Of Npcs In Arabidopsismentioning
confidence: 99%